Trampolines and Minefields: The Use of Touch during Home-Based Child Protection Visits in England. Issue 3 (27th May 2019) - Baeza, Samuel; Butler, Sarah; Smith, Sarah; McCray, Janet
Abstract : This paper is based on a research study which explores Social Workers' feelings about professionals touching children during statutory child protection visits to clients' homes in one part of a southern English county. The study focussed on Social Worker visits to children aged between two and ten years who were subject to child protection plans following Section 47 enquiries of the Children Act 1989. A convenience sample of ten completed questionnaires recorded the types of touch, which were reported during the last visit made by the social worker. Semi-structured interviews followed with a further ten Social Workers. Analysis of the data revealed that most of the Social Workers in the study did touch children in a range of ways and for a variety of reasons during visits. 'Touch' was a term which some found uncomfortable and this paper considers whether terminology obstructs open reflection on the topic. Practitioners were keen to discuss the subject more amongst their peers in order to share best practice.